Effect of number of oocytes and embryos on in vitro oocyte maturation, fertilization and embryo development in bovine - Salvador, I.; Cebrián-Serrano, Alberto; Salamone, D.; Silvestre, Miguel A. (2017)
The aim of this study was to identify the in vitro development stage at which the culture of a single or low number (n = 5 or 10) of oocytes/embryos could impair development in comparison with culture in group (n = 50). In the Experiment 1, it was confirmed that single in vitro embryo production yielded lower cleavage and blastocyst rates than in group (49.4 vs. 83.0%; 0% vs. 37.8%, respectively; p < 0.05). In Experiment 2 and 3, it was observed no effect on embryo development of culturing single or low number of oocytes during maturation and fertilization, respectively. In Experiment 4, it was observed a detrimental effect on blastocyst rate when cultured single or low number of embryos during post-fertilization in vitro culture (2.9; 10.2-10.8; 33.2% in single, low number of embryos (5-10), and control-grouped, respectively; p < 0.05). In Experiment 5, it was observed that the last part of the culture period (day 3 onwards) seemed to be more affected by the low number of embryos placed in culture. In conclusion, post-fertilization culture, especially on days 3 to 7 after fertilization, seems to be the most important stage for embryo development on single and/or low number (5-10) of embryos culture.